The economics of conservation area designation - Gabriel Ahlfeldt; Kristoffer Moeller; Sevrin Waights; Nicolai Wendland (European Regional Science Association (ERSA), 2013)
Provided that there are positive external benefits attached to the historic character of buildings, owners of properties in designated conservation areas benefit from a reduction in uncertainty regarding the future of their area. At the same time, the restrictions put in place to ensure the preservation of the historic character limit the degree to which properties can be altered and thus impose a cost to their owners. We test a simple theory of the designation process in which we postulate that the optimal level of designation is chosen so to Pareto-maximize the welfare of local owners. The implication of the model is that a) an increase in preferences for historic character should increase the likelihood of a designation and b) new designations at the margin should not be associated with significant house price capitalization effects. Our empirical results are in line with these expectations.
Keywords: R40; R58; 330; Heritage; Hedonic Modelling; Difference-in-Difference; Gentrification; England; Value